2018
DOI: 10.1021/acsinfecdis.7b00218
|View full text |Cite
|
Sign up to set email alerts
|

Toward More Drug Like Inhibitors of Trypanosome Alternative Oxidase

Abstract: New tools are required to ensure the adequate control of the neglected tropical disease human African trypanosomiasis. Annual reports of infection have recently fallen to fewer than 5000 cases per year; however, current therapies are hard to administer and have safety concerns and, hence, are far from ideal. Trypanosome alternative oxidase is an exciting target for controlling the infection; it is unique to the parasite, and inhibition of this enzyme with the natural product ascofuranone has shown to clear in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 31 publications
3
29
0
1
Order By: Relevance
“…Structure‐activity relationship of colletochlorin B. IC 50 values for the inhibition of purified recombinant trypanosome alternative oxidase reported by West et al and Saimoto et al (left and right IC 50 values, respectively)…”
Section: Progress In Chemical Scaffolds and Aox Inhibitor Developmentmentioning
confidence: 91%
See 4 more Smart Citations
“…Structure‐activity relationship of colletochlorin B. IC 50 values for the inhibition of purified recombinant trypanosome alternative oxidase reported by West et al and Saimoto et al (left and right IC 50 values, respectively)…”
Section: Progress In Chemical Scaffolds and Aox Inhibitor Developmentmentioning
confidence: 91%
“…After the groups of Kita, investigating the pharmacophore of AF ( 188 ), reported that the electron withdrawing cyano group was a useful alternative to its formyl group, West et al investigated the SAR of 3‐chloro‐4‐hydroxybenzonitrile analogues. With the aim of reducing the lipophilicity of the tail region of inhibitor 200 , and thereby improve its physicochemical properties including the predicted CNS multiparameter optimization score, they introduced different polar groups (amide and ether) in the lipophilic tail (Figure ) . A large decrease in inhibition potency compared with the n ‐octyl analogue ( 190 ) was observed with amide ( 191‐196 ) and ether groups ( 197‐199 ), showing that even minor increases in polarity in this part of the lipophilic tail are not tolerated.…”
Section: Progress In Chemical Scaffolds and Aox Inhibitor Developmentmentioning
confidence: 99%
See 3 more Smart Citations